MicroRNAs in Gingival Crevicular Fluid: An Observational Case-Control Study of Differential Expression in Periodontitis - Pedro J. Almiñana-Pastor; Francisco M. Alpiste-Illueca; Pablo Micó-Martinez; Jose Luis García-Giménez; Eva García-López; Andrés López-Roldán (Non-Coding RNA, 2023)
Objectives: microRNAs (miRNAs) present in the gingival crevicular fluid (GCF) of patients with chronic periodontitis may serve as biomarkers of periodontal disease. The aim of this study was to perform a miRNA-sequencing study of all miRNAs present in GCF, comparing miRNA expression level profiles between advanced chronic periodontitis (CP) patients and healthy subjects (HS). Materials and methods: GCF samples were collected from the single-rooted teeth of patients with severe CP (n = 11) and of HS (n = 12). miRNAs were isolated from GCF using an miRNeasy Serum/Plasma kit(Qiagen GmbH, Hilden, Germany). Reverse transcription polymerase chain reaction (qRT-PCR) was used to determine the expression levels of miRNA candidates involved in periodontal pathogenesis. Results: Of all the sequenced miRNAs, miR-199, miR-146a, miR-30a, and miR-338 were identified as best representing the CP patient samples. The validation study identified miR-199 as the most powerful biomarker used to define periodontitis. Conclusions: Upon sequencing all known miRNAs in GCF for the first time, we uncovered several potential biomarkers to define periodontitis. Identifying miRNAS in the GCF using high-throughput approaches will clarify the role of these molecules in periodontitis and provide biomarkers with potential applications.